Bacias hidrográficas e os conflitos pelos usos das águas no estado de Sergipe - Anézia Maria Fonseca Barbosa; Alberlene Ribeiro de Oliveira; Luiz Carlos Sousa Silva; Rosemeri Melo e Souza; Sindiany Suelen Caduda dos Santos (Confins)
This article evaluates the dynamics for the hydrographic basins in Sergipe, from socialenvironmental conflicts about the multiple uses of water. The qualitative approach research was developed upon bibliographic, documental and field research collections, between the years 2010 and 2018. The results reveal that the conflicts around the current dynamics of agriculture and cattle raising activities, the use of lands, industry, civil engineering, commerce, and other services, occur in an unsustainable way and will compromisse water supplies in the coming decades. In the long run, it becomes clear that the State, concerning water resource manegement policies, needs to come up with integrated actions, aiming the socialenvironmental sustainability of the hydrographic basins in Sergipe and minimization of the existing conflicts.